Without Tess - Pixley, Marcella (Farrar Straus Giroux, 2011)
Fifteen-year-old Lizzie Cohen recalls what it was like growing up with her imaginative but disturbed older sister Tess, and how she is striving to reclaim her own life since Tess died.